Expression of the Aldo-Ketoreductases AKR1B1 and AKR1B10 in Human Cancers - Laffin, Brian; Petrash, Mark (Frontiers in Pharmacology, 2012)
The American Cancer Society estimates that there will be more than 1.5 million new cases of cancer in 2011, underscoring the need for identification of new therapeutic targets and development of novel cancer therapies. Previous studies have implicated the human aldo-keto reductases AKR1B1 and AKR1B10 in cancer, and therefore we examined AKR1B1 and AKR1B10 expression across all major human cancer types using the Oncomine cancer gene expression database (Compendia Biosciences, www.oncomine.com). Using this database, we found that expression of of AKR1B1 and AKR1B10 varies greatly by cancer type and tissue of origin, including agreement with previous reports that AKR1B10 is significantly over-expressed in cancers of the lungs and liver. AKR1B1 is more broadly over-expressed in human cancers than AKR1B10, albeit at a generally lower magnitude. AKR1B1 over-expression was found to be associated with shortened patient survival in acute myelogenous leukemias and multiple myelomas. High AKR1B10 expression tends to predict less aggressive clinical course generally, notably within lung cancers, where it tends to be highly over-expressed compared to normal tissue. These findings suggest that AKR1B1 inhibitors in particular hold great potential as novel cancer therapeutics.